Analysis of poisonings in patients up to 18 years old hospitalized in the Clinical Department of Toxicology and Cardiology in Stefan Wyszyński Regional Specialist Hospital in Lublin in 2022 - Sosnowska, Weronika; Brzozowska, Aleksandra; Tchórz , Michał; Taracha, Kalina; Tkaczyk, Rafał; Tomczyk, Jakub; Tomkiewicz, Maciej; Środoń, Maria; Świątek, Gabriela; Śwital, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Poisoning in children and adolescents remain a serious medical, psychological and social problem. The aim of the study was to analyse poisonings in patients up to 18 years old admitted to the Clinical Department of Toxicology and Cardiology in Stefan Wyszyński Regional Specialist Hospital in Lublin in 2022. Material and method: The research was retrospective. Medical records of 120 cases of poisoning in patients up to the age of 18 were analysed. Results: In the studied period 120 patients from 13 to 18 years old were hospitalized due to intoxication, 84 (70%) of them were female and 36 (30%) of them were male. Majority of cases came from urban areas (69,2%). The most frequent causes of poisonings were medicaments (55%), drugs (29,2%) and alcohol (28,3%). The intentional intoxications were found in 113 (94,2%) cases, 45 (39,8%) of them were suicide attempt. Mental diseases were found in 71 (59,1%) cases, the most common one was depressive disorder. There were no deaths in the researched group. Conclusions: Because of the relevance of child patients poisoning young people should be provided with psychological care. Female teenagers must get special kind of support. The availability of child psychiatrists and psychologists is still too poor. Prohibition of selling alcohol to minors should be enforced stricly. It seems that acces to OTC drugs is way much too easy for people. There is a necessity of parents’education about children poisoning.